PHUBBING BEHAVIOR IN THE QUR’AN: A THEMATIC STUDY OF THE OPINIONS OF INDONESIAN MUFASSIR - Zanuba, Alisa Aura; Musolli, Musolli (Universitas Nurul Jadid, 2023)
This research is motivated by the widespread occurrence of phubbing activities in the surrounding environment. Phubbing, or phone snubbing, is a detrimental activity where individuals ignore their conversation partners and focus more on their handheld smartphones. This study aims to explore a profound understanding of phubbing behavior in the context of the Qur’an and to determine the Qur’an’s perspective on phubbing behavior. This research adopts a qualitative approach employing literature review methods (library research), with data derived from two sources: primary and secondary. Primary sources include interpretations by Indonesian scholars such as Quraish Shihab and Buya Hamka, while secondary sources consist of literature related to the discussion. The thematic method is also used to gather verses addressing phubbing behavior. The results of this research include: 1) Patterns of phubbing individuals spending time on games and addictive behaviors on gadgets. 2) Explanations about communication ethics in the Qur’an, where phubbing behavior can damage the quality of communication for individuals and their conversation partners. 3) Phubbing behavior can diminish the quality of time. And 4) It may lead to neglect of one’s surroundings